Protective Effects of Thalidomide on High-Glucose-Induced Podocyte Injury through In Vitro Modulation of Macrophage M1/M2 Differentiation - Hui Liao; Yuanping Li; Xilan Zhang; Xiaoyun Zhao; Dan Zheng; Dayue Shen; Rongshan Li (Journal of Immunology Research)
Objective. It has been shown that podocyte injury represents an important pathological basis that contributes to proteinuria and eventually leads to kidney failure. High glucose (HG) activates macrophage polarization, further exacerbating HG-induced podocyte injury. Our previous study on diabetic nephropathy rats indicated that thalidomide (Tha) has renoprotective properties. The present study explored the effects of Tha on mRNA and protein expressions of inducible nitric oxide synthase (iNOS), tumor necrosis factor- (TNF-) α, mannose receptor (CD206), and arginase- (Arg-) 1 in HG-activated macrophages. iNOS and TNF-α are established as markers of classically activated macrophage (M1). CD206 and Arg-1 are regarded as markers of alternatively activated macrophages (M2). During the experiment, the supernatants of (HG)-treated and (Tha)-treated macrophages, designated as (HG) MS and (Tha) MS, were simultaneously collected and processed. TNF-α and interleukin- (IL-) 1β levels as well as protein expressions of nephrin and podocin in HG, (HG) MS, and (Tha) MS-cultured podocytes were evaluated. The results showed that compared to the 11.1 mM normal glucose (NG), the 33.3 mM HG-cultured RAW 264.7 cells exhibited upregulated iNOS and TNF-α mRNAs and protein expressions, and downregulated CD206 and Arg-1 expressions significantly (p<0.05). Tha 200 μg/ml suppressed iNOS and TNF-α, and promoted CD206 and Arg-1 expressions significantly compared to the HG group (p<0.05). Furthermore, (HG) MS-treated podocytes showed an increase in TNF-α and IL-1β levels and a downregulation in nephrin and podocin expression significantly compared to NG-treated and HG-treated podocytes (p<0.05). The (Tha 200 μg/ml) MS group exhibited a decrease in TNF-α and IL-1β level, and an upregulation in nephrin and podocin expressions significantly compared to the (HG) MS group (p<0.05). Our research confirmed that HG-activated macrophage differentiation aggravates HG-induced podocyte injury in vitro and the protective effects of Tha might be related to its actions on TNF-α and IL-1β levels via its modulation on M1/M2 differentiation.